Results on Binary Soft Topological Spaces - P. G. Patil; Asha G. Adaki (Ratio Mathematica, 2023)
The Baire space is used in the proof of results in many areas of analysis and geometry, including some of the fundamental theorems of functional analysis. The concept of Baire spaces has been studied extensively in general topology. Thangaraj and Anjalmose [35] studied Baire spaces in the context of fuzzy theory. In this paper, we discussed the notions of the binary soft nowhere dense, binary soft dense, binary soft Gδ-set, binary soft first and second category sets, binary soft Baire spaces. Many of their properties are revealed and different characterizations of each are given. In conclusion, we determined some conditions under which the subspace property of a Baire space is preserved.